Resource management at local level: "platform" approach for integration - Pant, Dhruba; Sharma, K. R. (2010)
Traditionally, the users? organisations at local level are playing an important role for the management of natural resources by organizing the users. The Government of Nepal through its Water Resources Strategy 2002 and National Water Plan 2005 has emphasized a holistic approach in place of sectoral one for natural resources management at sub/basin level based on the principle of Integrated Water Resources Management (IWRM). It envisages the creation of committee at the sub/basin level, which is lacking at present. But both vertical and horizontal linkage between institutions and among the various water users is sectoral. Therefore, an action research was carried out in Nepal and India to examine the possibility of up-scaling the role of existing natural resource users? group and other stakeholders - local elected institutions and I/NGOs in order to facilitate the evolvement of institution at sub/basin level. The information was collected through checklist in focused group discussions, consultation workshop at the local and district level with Water users group, Forest Users Group and other stakeholders. The dynamics of resource management along with stakeholders? role and processes/methods followed in ?Platform? formation, which is expected to evolve as sub/basin level institutions for IWRM in Nepal and its future is dealt in this paper.